Analysis of the fiscal performance of argentinian provinces - Vargas Ochuza, Emilse Nancy (Ediciones UNL. Secretaría de Extensión de la UNL, 2021)
The objective of this research is to analyze the fiscal performance of each of the 23 Argentinian provinces, together with the Autonomous City of Buenos Aires, during the 1988-2018 period. The results show that almost all of them have a procyclical fiscal policy, in line with the behavior of the country at the national level. On the other hand, a theoretical model is detailed to show how discretionary transfers by the federal government generate a strategic relationship among the provinces. Its results serve as support for an empirical analysis of the transfers and the possible creation of a countercyclical reserve fund based on them. The latter will be carried out as a complement in a future research work.